Family-friendly jobs and occupational sorting across gender: Evidence from introduction of a maximum 40-hour workweek - Kathrine Aaby Lorentzen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
I study the impact of changes in the family-friendliness of jobs on occupational choice across gender in the labor market for physicians. I utilize a Danish working hour reform from 1981, which imposed a maximum 40-hour workweek for junior hospital physicians. To do so, I digitize archival data and combine it with administrative data. I find that the reform affected some specialties more than others, with the least flexible (acute) specialties being the most affected. I exploit these differing treatment intensities across specialties in order to estimate the impact of family-friendly hours constraints on specialty choice across gender in a dose-response difference-in-differences design. My results suggest that the fraction of females in a specialty increased more where introduction of a 40-hour workweek had more bite. In addition, I find that female fertility increased more in highly affected specialties. I do not find similar effects for males. My results suggest that preferences for working hours are important for occupational choice across gender and hence gender inequality in wages.
Keywords: 330